Broadening sound absorption coefficient with hybrid resonances. (March 2020) - Bucciarelli, F.; Meo, M.
Abstract: In the last years, a great research effort has been focused on the noise mitigation at low frequencies. Membrane-type acoustic metamaterials (AMM) are one of the most promising solutions to meet the growing demand for low frequency sound absorbers. Typically, acoustic membrane absorbers require large back cavities to achieve low frequency sound absorption, which is usually categorised by a single narrow absorption peak. This paper presents an acoustic resonator unit cell, comprising of a thin elastic silicone plate with an air gap cavity with broadband absorption in a frequency range between 250 and 400 Hz. The broadband and multiple peak sound absorption showed by the proposed resonator is due to hybrid resonances which occur in the frequency range due to coupling of the structural dynamic response of the plate with the acoustic response of the air cavity. A numerical model based on acoustic-structural interaction, validated for experimental data, has been used to explain how the broadening gain in the sound absorption level is strictly related to the hybrid resonances of the unit cell resonator. We demonstrated that hybrid resonances are a function of the geometrical parameters and the ratio between the Young's modulus and the density of the material plate, thus the proposed resonators absorption frequency range is tuneable at low frequencies allowing a wider broadband not achievable with acoustic membrane absorbers.